Analisis Vegetasi Tumbuhan Liar Yang Berpotensi Sebagai Refugia Di Area Pertanian Padi Kecamatan Jombang Untuk Penyusunan E-Katalog - Achmad, Nora Iffatul Maula; Wulandari, Anggun; Meishanti, Ospa Pea Yuanita (CV. Information Technology Training Center - Indonesia (ITTC), 2023)
There are several agricultural areas in Denanyar Village, Jombang District. large distribution of refugia The purpose of this research is to explain the types of plants. wild, which has the potential to be a refugia in the rice farming area of Jombang District, explain relative density (KR), relative frequency (FR), relative dominance (DR), and important value index (INP) of refugia in the rice farming area of Jombang District and find out the results of the preparation of the e-catalog from the results of the analysis of plant vegetation. wild, which has the potential to be a refugia in the rice farming area of Jombang District. This study uses a quadratic sampling method with a plot size of 10 m x 10 m, which totals 10 plots. Results of research on plant vegetation analysis wild, which has the potential to be a refugia in the rice farming area of Jombang District. For the development of e-catalog teaching materials, 338 individuals, consisting of 11 plants, including: Mimosa pudica (Embarrassed Daughter), Eleusine indica (Grass reeds), Ricardia scarbra (coarse clover), Digitaria ciliaris (kebo grass), Ipomoea quamiochit (Earth detail), Amaranthus (Spinach thorn), Euphorbia hirta L. (Patikan seeds), green poinsettia (Green Kastuba), Bidens pilosa (Ajeran), and Ipomoea obscura (star white kale), and Ipomoea aquatica (Kangkung). The refugia Dominating the rice farming area is Eleusine indica (Grass Lulangan). Because in each plot there are these plants, so the relative density 100%, and the highest important value index (INP) at the weed level is 132.366%, while the level of shrubs is 88.145%. Research results later developed into an e-catalog that explains the types of wild plants that are potential as a refugia consisting of 11 plants consisting of Mimosa pudica (Embarrassed Daughter), Eleusine indica (Palm Grass), Ricardia scarbra (coarse clover), Digitaria ciliaris (kebo grass), and Ipomoea quamiochit (detailed earth), Amaranthus (spinach spines), Euphorbia hirta L. (patikan seeds), Green poinsettia (green Kastuba), Bidens pilosa (Ajeran), and Ipomoea obscura (Kale) white star), Ipomoea aquatica (Kangkung), along with its classification and description Morphologically, the e-catalog was developed with Wordpress.